Direct transfer of micro-molded electrodes for enhanced mass transport and water management in PEMFC - Deshmukh, Ashvini B.; Kale, Vinayak S.; Dhavale, Vishal M.; Sreekumar, K.; Vijayamohanan, K.; Shelke, Manjusha V. (Electrochemistry Communications, 2010)
Soft lithography technique is used to micropattern the electrodes on the electrolyte membrane of polymer electrolyte fuel cell (PEMFC) in order to alleviate the issues due to poor water management and inadequate reactant distribution in the fuel cell environment. Membrane electrode assembly with the micropatterned electrode has shown an increase in power density at a higher temperature as well as at a higher relative humidity when compared to a flat electrode. Consistency in cell performance is observed in the case of micropatterned electrodes. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Bipolar plate-less PEM fuel cell; Micropatterned electrodes; Microtransfer molding; Soft lithography

High pt utilization electrodes for polymer electrolyte membrane fuel cells by dispersing pt particles formed by a preprecipitation method on carbon ``polished'' with polypyrrole - Unni, SreeKuttan M.; Dhavale, Vishal M.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2010)
Pt utilization on carbon black (CB) has been significantly improved by initially utilizing polypyrrole (PPy) as a moiety to ``polish'' the carbon surface and subsequently by dispersing Pt particles formed by a preprecipitation process to minimize their migration into the geometrically restricted areas of the carbon surface. This process strategy has helped to significantly extend the triple-phase boundary as a greater number of Pt particles comes in direct contact with Nafion, leading to a substantial improvement in the overall catalyst utilization. Preliminary analyses such as IR, thermogravimetric analysis, and N(2) sorption confirmed the presence of PPy on the surface. Approximately 50% reduction in the surface area of CB after the controlled in situ polymerization of pyrrole monomer on the carbon surface indicated preferential filling and coverage of pores and other geometrically restricted pockets of carbon surface. On the other hand, by converting Pt into colloids in the preprecipitation method prior to their reduction, the platinum particles are forced to stay on the hybrid support; a major part of which otherwise would have been migrated into the surface pores and defect sites. Platinum particle size on these hybrid supports is 2 times higher than the catalyst prepared by polyol process. However, the electroactive surface area and mass activity are 2 times higher than that of the Pt particles prepared by polyol on hybrid material and are also significantly higher than that of the conventional electrocatalysts prepared by the polyol method. At 0.8 V, the kinetic current density (j(k)) of Pt/C-PPy-Pre obtained from the Koutecky-Levich plot is 1.5 and 2.5 times higher than that of catalysts prepared by the polyol method on PPy-coated carbon and Vulcan XC-72 carbon, respectively. Almost 210 and 160 mW cm(-2) improvement for the maximum power density, respectively with oxygen and air, was obtained with the modified system in comparison to the conventional system when the single cell evaluations were carried out at 60 degrees C with a Pt loading of 0.5 mg cm(-2) in the anode and cathode sides. This enhancement in the cell performance under the two different oxygen partial pressure conditions clearly emphasizes the improved oxygen reduction reaction (ORR) and mass-transfer characteristics of the hybrid electrode material compared to the other catalysts.

Ex-situ dispersion of core-shell nanoparticles of Cu-Pt on an in situ modified carbon surface and their enhanced electrocatalytic activities - Dhavale, Vishal M.; Unni, SreeKuttan M.; Kagalwala, Husain N.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Chemical Communications, 2011)
Direct dispersion of core-shell nanoparticles on a carbon support (Cu@ Pt/C) has been achieved while retaining the essential core-shell features of the nanoparticles by adopting an in situ surface modification-cum-anchoring strategy.

Morphology controlled synthesis of LiV(2)0(5)/Ag nanocomposite nanotubes with enhanced electrochemical performance - Diggikar, Rahul S.; Dhavale, Vishal M.; Shinde, Dhanraj B.; Kanbargi, Nihal S.; Kulkarni, Milind V.; Kale, Bharat B. (RSC Advances, 2012)
Uniformly embedded silver (Ag) nanoparticles in orthorhombic nanotubes (NTs) of lithium vanadium oxide (LVO) synthesized via a facile template-free hydrothermal treatment at low temperature exhibited an excellent morphology with good crystallinity and may act as an exceptional contender for electronic applications.

Tuning the performance of low-Pt polymer electrolyte membrane fuel cell electrodes derived from Fe2O3@Pt/C core-shell catalyst prepared by an in situ anchoring strategy - Dhavale, Vishal M.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2012)
A low-Pt electrode with high performance and durability characteristic has been realized for polymer electrolyte membrane fuel cell applications from a carbon-supported Fe2O3@Pt core-shell catalyst prepared by a process involving in situ surface modification-cum-anchoring strategy. The process is based on an in-house-developed methodology for generating and interlocking the core-shell nanoparticles on the surface of the carbon substrate, which undergoes functionalization in the reaction medium itself by the intervention of the reducing agent employed in the reaction. Ascorbic acid, which was used as the reducing agent in the process, played a crucial role by making use of its multifunctional activities as reducing agent, stabilizing agent, as well as capping agent in addition to its efficiency in functionalizing the carbon surface during the course of the reaction. The formation of core-shell nanostructures could be confirmed by XRD, HR-TEM, and cyclic voltammetric analysis. The oxygen reduction property and the performance during the single cell evaluations were found to be strongly influenced by the thickness of the catalyst layer owing to the ohmic contribution from the higher mass fraction of the less conductive Fe2O3 core. However, when the thickness of the catalyst layer was kept within the threshold level, Fe2O3@Pt catalyst clearly outperforms the commercial Pt/C catalyst. This benefit of the core-shell catalyst enabled it to display a maximum power density of 900 mW/cm(2) with a significantly low cathode Pt loading of 0.05 mg/cm(2). An accelerated durability assessment of the membrane electrode assembly for 10 h gave consistent performance characteristics. The study gave convincing evidence on the feasibility of using the electrodes derived from the core-shell catalyst prepared by the in situ anchoring strategy for developing cost competitive systems and miniature cells for niche applications.

Porous-organic-framework-templated nitrogen-rich porous carbon as a more proficient electrocatalyst than Pt/C for the electrochemical reduction of oxygen - Pachfule, Pradip; Dhavale, Vishal M.; Kandambeth, Sharath; Kurungot, Sreekumar; Banerjee, Rahul (Chemistry-A European Journal, 2013)
Porous nitrogen-rich carbon (POF-C-1000) that was synthesized by using a porous organic framework (POF) as a self-sacrificing host template in a nanocasting process possessed a high degree of graphitization in an ordered structural arrangement with large domains and well-ordered arrays of carbon sheets. POF-C-1000 exhibits favorable electrocatalytic activity for the oxygen-reduction reaction (ORR) with a clear positive shift of about 40 mV in the onset potential compared to that of a traditional, commercially available Pt/C catalyst. In addition, irrespective of its moderate surface area (785 m2?g-1), POF-C-1000 showed a reasonable H2 adsorption of 1.6 wt?% (77 K) and a CO2 uptake of 3.5 mmol?g-1 (273 K).
Keywords: Adsorption; Electrochemistry; fuel cells; oxygen-reduction reaction; porous organic frameworks

Activated nitrogen doped graphene shell towards electrochemical oxygen reduction reaction by its encapsulation on Au nanoparticle (Au@N-Gr) in water-in-oil ``nanoreactors'' - Dhavale, Vishal M.; Gaikwad, Sachin S.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2014)
Encapsulation of nitrogen doped graphene on Au nanoparticle (Au@N-Gr) could be accomplished through a water-in-oil emulsion technique, where the emulsion droplets act as `nanoreactors' and the redox reaction inside the droplets results in the formation of core-shell nanoparticles. The encapsulation of N-Gr on a small quantity of Au (N-Gr : Au wt ratio of 90 : 10) made the N-Gr layer more conductive and active towards electrochemical oxygen reduction reaction (ORR). The enhanced conductivity helped the system narrow down the ohmic overpotential, and direct electronic interactions between the Au and Gr layers brought in a favourable positive shift to the onset potential for ORR. Encapsulation has helped N-Gr reduce the overpotential by similar to 121 mV as compared to N-Gr alone. Apart from this, the oxygen reduction kinetics of Au@N-Gr also appeared to be superior to N-Gr and Au nanoparticles as separate entities due to greater involvement of the preferred 4-electron reduction pathway. At -0.3 V (vs. Hg/HgO), the percentage of hydrogen peroxide (H2O2) (a product formed from the undesirable 2-electron reduction pathway) was found to be 16.5% for Au@Gr, where Au was covered with undoped Gr, which gets reduced to a significantly low level of 6.5% for Au@N-Gr. Au and N-Gr as separate entities give yield of H2O2 as 52.2 and 47.7%, respectively. From these, it can be concluded that the coverage of N-Gr on Au helps decrease the yield of H2O2 drastically apart from the benefits of synergistic interactions in reducing both ohmic and activation overpotentials.

Nitrogen-doped graphene interpenetrated 3D Ni-nanocages: efficient and stable water-to-dioxygen electrocatalysts - Dhavale, Vishal M.; Gaikwad, Sachin S.; George, Leena; Devi, R. Nandini; Kurungot, Sreekumar (Nanoscale, 2014)
Herein, we report the synthesis of a nitrogen-doped graphene (NGr) interpenetrated 3D Ni-nanocage (Ni-NGr) electrocatalyst by a simple water-in-oil (w/o) emulsion technique for oxidation of water to dioxygen. Correlation of adsorption of NGr and subsequent interpenetration through the specific surface plane of nickel particles as well as the concomitant interaction of N and C with Ni in the nano-regime has been investigated. Apart from the benefits of the synergistic interactions between Ni, N, and C, the overall integrity of the structure and its intra-molecular connectivity within the framework help in achieving better oxygen evolution characteristics at a significantly reduced overpotential. The engineered Ni-NGr nanocage displays a substantially low overpotential of similar to 290 mV at a practical current density of 20 mA cm(-2) in 0.1 M KOH. In comparison, NGr and Ni-particles as separate entities give overpotentials of similar to 570 and similar to 370 mV under similar conditions. Moreover, the long term stability of Ni-NGr was investigated by anodic potential cycling for 500 cycles and an 8.5% increment in the overpotential at 20 mA cm(-2) was observed. Additionally, a chronoamperometric test was performed for 15 h at 20 mA cm(-2), which highlights the better sustainability of Ni-NGr under the actual operating conditions. Finally, the quantitative estimation of evolved oxygen was monitored by gas chromatography and was found to be 70 mmol h(-1) g(-1) of oxygen, which is constant in the second cycle as well.

Structure and dynamics of benzyl-NX3 (X = Me, Et) trifluoromethanesulfonate ionic liquids - Sunda, Anurag Prakash; Dhavale, Vishal M.; Kurungot, Sreekumar; Venkatnathan, Arun (Journal of Physical Chemistry B, 2014)
Ammonium-based benzyl-NX3 (X = methyl, ethyl) trifluoromethanesulfonate (TFA) ionic liquids (ILs) are low cost, nontoxic, thermally stable ion-conducting electrolytes in fuel cells and batteries. In the present study, we have characterized the structure and dynamics of these ILs using molecular dynamics (MD) simulations and ionic conductivity using electro-chemical impedance spectroscopy (EIS) at varying temperature and relative humidity (RH). Results from MD simulations predict that cation-cation and cation-anion interactions are stronger in benzyltrimethylammonium (BzTMA) compared to benzyltriethylammonium (BzTEA) that diminish with increase in RH. Further, the BzTMA cations show both C-H/Ph (center of mass of phenyl ring) and cation-Ph interactions whereas BzTEA cations show only strong cation-Ph interactions. The C-H/Ph interactions (psi >= 90 degrees, d(H-Ph) <= 4 angstrom, theta < 50 degrees and d(C.Ph) <= 4.3 angstrom) in BzTMA cations increase with RH and are highest at RH = 90%. The cumulative impact of electrostatic, cation/Ph, and C-H/Ph interactions results in lower conductivity of BzTMA-TFA IL compared to BzTEA-TFA IL. The EIS measurements show that the trends in ionic conductivity of ILs at RH = 30 and 90% are qualitatively similar to the Nernst-Einstein conductivity from MD simulations. The ionic conductivity of BzTEA-TFA IL is similar to 3 times higher than BzTMA-TFA IL at 353 K and RH = 90%.

Can enantiomer ligands produce structurally distinct homochiral MOFs? - Dubey, Mrigendra; Kumar, Ashish; Dhavale, Vishal M.; Kurungot, Sreekumar; Pandey, Daya Shankar (CrystEngComm, 2015)
Here, we report a self-assembled homochiral metal-organic framework [Cu-1.5(H2LL-leu)(Ac)H2O](n)center dot 3H(2)O (1) obtained from an L-leucine-derived ligand (H4L(L-leu)) and Cu(Ac)(2)center dot H2O in a 1 : 1 ratio. Coordination-induced conformational change in the ligand has been monitored by circular dichroism which has been further attested by synthesizing a D-leucine-containing enantiomer H4L D-leu and its Cu(II) complex [Cu-1.5(H2LD-leu)H2O](n)center dot 10H(2)O (2). Structure determination revealed entirely different structures for the homochiral MOFs (1 and 2) obtained from the L/D-leucine-derived enantiomer ligands under analogous reaction conditions. Further, structural dissimilarity in these MOFs has been judicially supported by proton conductance studies. MOF 1 shows higher proton (10(-5) S cm(-1)) conductance in comparison to 2 (10(-6) S cm(-1)) due to dissimilar alignment of the hydrogen-bonded water molecules in the hydrophilic pocket as well as crystal packing.

Cu-Pt nanocage with 3-D electrocatalytic surface as an efficient oxygen reduction electrocatalyst for a primary Zn-air battery - Dhavale, Vishal M.; Kurungot, Sreekumar (ACS Catalysis, 2015)
Cu-Pt nanocage (CuPt-NC) intermetallic structures have been prepared by an in situ galvanic displacement reaction. The structures are found to be well organized within the framework demarcated with distinguishing arms, having clear edges and corners with a size of similar to 20 nm. The unique nanocage structure possessing large specific surface area and better structural integrity helps to achieve improved electrochemical oxygen reduction reaction activity and stability in alkaline solution in comparison to the commercially available 20 wt % Pt/C. CuPt-NC shows 50 mV positive onset potential shift with significantly higher limiting current in comparison to Pt/C. Interestingly, CuPt-NC has shown 2.9- and 2.5-fold improved mass activity and specific activity, respectively, for ORR at 0.9 V vs RHE in comparison to Pt/C. Moreover, the stability of CuPt-NC has been tested by an accelerated durability test under alkaline conditions. CuPt-NC has been subsequently utilized as the air electrode in a primary Zn-air battery and is found to possess 1.30- and 1.34-fold improved power density and current density at 1 V, respectively, in comparison to the state-of-the-art Pt/C catalyst. In addition, CuPt-NC has shown several hours of constant discharge stability at 20 mA cm(-2) with a specific capacity of 560 mAh gZn(-1) and energy density of 728 Wh kgZn(-1) in the primary Zn-air battery system.
Keywords: 3-D electrocatalytic surface; Cu-Pt nanocage; electrocatalyst; galvanic displacement; oxygen reduction reaction; solvothermal method; Zn-air battery

Electrochemical preparation of nitrogen-doped graphene quantum dots and their size-dependent electrocatalytic activity for oxygen reduction - Shinde, Dhanraj B.; Dhavale, Vishal M.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Bulletin of Materials Science, 2015)
Here we report a remarkable transformation of nitrogen-doped multiwalled carbon nanotubes (MWCNTs) to size selective nitrogen-doped graphene quantum dots (N-GQDs) by a two-step electrochemical method. The sizes of the N-GQDs strongly depend on the applied anodic potential, moreover increasing potential resulted in a smaller size of N-GQDs. These N-GQDs display many unusual size-dependant optoelectronic (blue emission) and electrocatalytic (oxygen reduction) properties. The presence of N dopants in the carbon framework not only causes faster unzipping of MWCNTs but also provides more low activation energy site for enhancing the electrocatalytic activity for technologically daunting reactions like oxygen reduction. The smaller size of N-GQDs has shown better performance as compared to the large N-GQDs. Interestingly, N-GQDs-3 (size = 2.5 +/- 0.3 nm, onset potential = 0.75 V) show a 30-mV higher positive onset potential shift compared to that of N-GQDs-2 (size = 4.7 +/- 0.3 nm, onset potential = 0.72 V) and 70 mV than that of N-GQDs-1 (size = 7.2 +/- 0.3, onset potential = 0.68 V) for oxygen reduction reaction (ORR) in a liquid phase. These result in the size-dependent electrocatalytic activity of N-GQDs for ORR as illustrated by the smaller sized N-GQDs (2.5 +/- 0.3 nm) undoubtedly promising metal-free electrocatalysts for fuel cell applications.
Keywords: fuel cells; MWCNTs; N-GQDs; oxygen reduction reaction; unzipping

Ionic conductivity probed in main chain liquid crystalline azobenzene polyesters - Nardele, Chinmay G.; Dhavale, Vishal M.; Sreekumar, K.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2015)
Three main chain thermotropic liquid crystalline (LC) azobenzene polymers were synthesized using the azobenzene twin molecule (P4P) having the structure Phenylazobenzene-tetraethyleneglycol-Phenylazobenzene as the AA monomer and diols like diethylene glycol, tetraethylene glycol (TEG), and hexaethylene glycol as the BB comonomer. Terminal C(O)OMe units on P4P facilitated transesterification with diols to form polyesters. All polymers exhibited stable smectic mesophases. One of the polymers, Poly(P4PTEG) was chosen to prepare composite polymer electrolytes with LiCF3SO3 and ionic conductivity was measured by ac impedance spectroscopy. The polymer/0.3 Li salt complex exhibited a maximum ionic conductivity in the range of 10(-5) S cm(-1) at room temperature (25 degrees C), which increased to 10(-4) S cm(-1) above 65 degrees C. The temperature dependence of ionic conductivity was compared with the phase transitions occurring in the sample and it was observed that the glass transition had a higher influence on the ionic conductivity compared to the ordered LC phase. Reversible ionic conductivity switching was observed upon irradiation of the polymer/0.3 Li salt complex with alternate UV and visible irradiation. (c) 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 629-641
Keywords: azo polymers; glass transition; liquid-crystalline polymers (LCP)

Lithium-assisted proton conduction at 150 degrees C in a microporous triazine-phenol polymer - Nandi, Shyamapada; Dhavale, Vishal M.; Shalini, Sorout; Werner-Zwanziger, Ulrike; Singh, Harpreet; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Materials Interfaces, 2015)
Keywords: conduction; hydrophobic polar frameworks; lithiated polymers; proton conduction; triazine-phenol polymers

Nanocrystalline Fe-Fe2O3 particle-deposited N-doped graphene as an activity-modulated Pt-free electrocatalyst for oxygen reduction reaction - Dhavale, Vishal M.; Singh, Santosh K.; Nadeema, Ayasha; Gaikwad, Sachin S.; Kurungot, Sreekumar (Nanoscale, 2015)
The size-controlled growth of nanocrystalline Fe-Fe2O3 particles (2-3 nm) and their concomitant dispersion on N-doped graphene (Fe-Fe2O3/NGr) could be attained when the mutually assisted redox reaction between NGr and Fe3+ ions could be controlled within the aqueous droplets of a water-in-oil emulsion. The synergistic interaction existing between Fe-Fe2O3 and NGr helped the system to narrow down the overpotential for the oxygen reduction reaction (ORR) by bringing a significant positive shift to the reduction onset potential, which is just 15 mV higher than its Pt-counterpart. In addition, the half-wave potential (E-1/2) of Fe-Fe2O3/NGr is found to be improved by a considerable amount of 135 mV in comparison to the system formed by dispersing Fe-Fe2O3 nanoparticles on reduced graphene oxide (Fe-Fe2O3/RGO), which indicates the presence of a higher number of active sites in Fe-Fe2O3/NGr. Despite this, the ORR kinetics of Fe-Fe2O3/NGr are found to be shifted significantly to the preferred 4-electron-transfer pathway compared to NGr and Fe-Fe2O3/RGO. Consequently, the H2O2% was found to be reduced by 78.3% for Fe-Fe2O3/NGr (13.0%) in comparison to Fe-Fe2O3/RGO (51.2%) and NGr (41.0%) at -0.30 V (vs. Hg/HgO). This difference in the yield of H2O2 formed between the systems along with the improvements observed in terms of the oxygen reduction onset and E-1/2 in the case of Fe-Fe2O3/NGr reveals the activity modulation achieved for the latter is due to the coexistence of factors such as the presence of the mixed valancies of iron nanoparticles, small size and homogeneous distribution of Fe-Fe2O3 nanoparticles and the electronic modifications induced by the doped nitrogen in NGr. A controlled interplay of these factors looks like worked favorably in the case of Fe-Fe2O3/NGr. As a realistic system level validation, Fe-Fe2O3/NGr was employed as the cathode electrode of a single cell in a solid alkaline electrolyte membrane fuel cell (AEMFC). The system could display an open circuit voltage (OCV) of 0.73 V and maximum power and current densities of 54.40 mW cm(-2) and 200 mA cm(-2), respectively, which are comparable to the performance characteristics of a similar system derived by using 40 wt% Pt/C as the cathode electrode.

Surface-tuned Co3O4 nanoparticles dispersed on nitrogen-doped graphene as an efficient cathode electrocatalyst for mechanical rechargeable zinc-air battery application - Singh, Santosh K.; Dhavale, Vishal M.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
The most vital component of the fuel cells and metal air batteries is the electrocatalyst, which can facilitate the oxygen reduction reaction (ORR) at a significantly reduced overpotential. The present work deals with the development of surface-tuned cobalt oxide (Co3O4) nanoparticles dispersed on nitrogen-doped graphene as a potential ORR electrocatalyst possessing some unique advantages. The thermally reduced nitrogen-doped graphene (NGr) was decorated with three different morphologies of Co3O4 nanoparticles, viz., cubic, blunt edged cubic, and spherical, by using a simple hydrothermal method. We found that the spherical Co3O4 nanoparticle supported NGr catalyst (Co3O4-SP/NGr-24h) has acquired a significant activity makeover to display the ORR activity closely matching with the state-of-the-art Pt supported carbon (PtC) catalyst in alkaline medium. Subsequently, the Co3O4-SP/NGr-24h catalyst has been utilized as the air electrode in a Zn-air battery, which was found to show comparable performance to the system derived from PtC. Co3O4-SP/NGr-24h catalyst has shown several hours of flat discharge profile at the discharge rates of 10, 20, and 50 mA/cm(2) with a specific capacity and energy density of similar to 590 mAh/g(-zn) and,840 Wh/kg(-zn), respectively, in the primary Zn-air battery system. In conjunction, Co3O4-SP/NGr-24h has outperformed as an air electrode in mechanical rechargeable Zn-air battery as well, which has shown consistent flat discharge profile with minimal voltage loss at a discharge rate of 50 mA/cm(2). The present results, thus demonstrate that the proper combination of the tuned morphology of Co3O4 with NGr will be a promising and inexpensive material for efficient and ecofriendly cathodes for Zn-air batteries.
Keywords: electrocatalyst; mixed facets; oxygen reduction reaction; rechargeable zinc-air battery; surface morphology

1000-fold enhancement in proton conductivity of a MOF using post-synthetically anchored proton transporters - Shalini, Sorout; Dhavale, Vishal M.; Eldho, Kavalakal Mathai; Kurungot, Sreekumar; Ajithkumar, Thalasseril G.; Vaidhyanathan, Ramanathan (Scientific Reports, 2016)
Pyridinol, a coordinating zwitter-ionic species serves as stoichiometrically loadable and non-leachable proton carrier. The partial replacement of the pyridinol by stronger hydrogen bonding, coordinating guest, ethylene glycol (EG), offers 1000-fold enhancement in conductivity (10(-6) to 10(-3) Scm(-1)) with record low activation energy (0.11 eV). Atomic modeling coupled with C-13-SSNMR provides insights into the potential proton conduction pathway functionalized with post-synthetically anchored dynamic proton transporting EG moieties.

Low-overpotential electrocatalytic water splitting with noble-metal-free nanoparticles supported in a sp(3) n-rich flexible COF - Mullangi, Dinesh; Dhavale, Vishal M.; Shalini, Sorout; Nandi, Shyamapada; Collins, Sean; Woo, Tom; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2016)
Covalent organic frameworks (COFs) are crystalline organic polymers with tunable structures. Here, a COF is prepared using building units with highly flexible tetrahedral sp(3) nitrogens. This flexibility gives rise to structural changes which generate mesopores capable of confining very small (<2 nm sized) non-noble-metal-based nanoparticles (NPs). This nanocomposite shows exceptional activity toward the oxygen-evolution reaction from alkaline water with an overpotential of 258 mV at a current density of 10 mA cm(-2). The overpotential observed in the COF-nanoparticle system is the best in class, and is close to the current record of approximate to 200 mV for any noble-metalfree electrocatalytic water splitting system-the Fe-Co-Ni metal-oxide-film system. Also, it possesses outstanding kinetics (Tafel slope of 38.9 mV dec(-1)) for the reaction. The COF is able to stabilize such small-sized NP in the absence of any capping agent because of the COF-Ni(OH)(2) interactions arising from the N-rich backbone of the COF. Density-functional-theory modeling of the interaction between the hexagonal Ni(OH)(2) nanosheets and the COF shows that in the most favorable configuration the Ni(OH)(2) nanosheets are sandwiched between the sp(3) nitrogens of the adjacent COF layers and this can be crucial to maximizing their synergistic interactions.

Reduced graphene oxide modified electrodes for sensitive sensing of gliadin in food samples - Chekin, Fereshteh; Singh, Santosh K.; Vasilescu, Alina; Dhavale, Vishal M.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (ACS Sensors, 2016)
Incidences of food allergies are on the rise, which can greatly affect the well-being of children as well as adults. Intolerance to gluten, a protein composite of gliadin and glutenin, present in wheat, barley, and rye and several cereals, can be the causative agent of celiac disease (CD) and other allergic reactions. A gluten-free diet has become essential for people affected by CD, and consequently, the amount of gluten in food products needs to be strictly controlled. In this paper, we report an electrochemical label-free immunosensor for ultrasensitive and specific detection of gliadin. The sensor takes advantage of the specific properties of porous reduced graphene oxide (prGO) covalently functionalized with anti-gliadin antibodies using 1-pyrenecarboxylic acid as linker molecule. Using differential pulse voltammetry (DPV) and [Fe(CN)6](3-/4-) as a redox probe, a decrease of current is linked to the presence of gliadin. The sensor achieved a detection limit of 1.2 ng mL(-1) over a 1.2-34 ng mL(-1) linear range with high selectivity. The advantages offered by this sensor are the possibility to regenerate the surface of the immunosensor, its rapid and ease of production, as well as applicability for the screening of gliadin concentrations in real food samples, as shown here.
Keywords: anti-gliadin antibody; food samples; gliadin; Immunosensor; Porous reduced graphene oxide

Strategic Preparation of Efficient and Durable NiCo Alloy Supported N-Doped Porous Graphene as an Oxygen Evolution Electrocatalyst: A Theoretical and Experimental Investigation - Singh, Santosh K.; Kumar, Deepak; Dhavale, Vishal M.; Pal, Sourav; Kurungot, Sreekumar (Advanced Materials Interfaces, 2016)
Development of an efficient and durable water splitting electrocatalyst holds a great commitment for the future energy devices. The real application of oxygen evolution reaction (OER) catalysts mainly suffers from sluggish kinetics and high overpotential except for the Ir and Ru-based systems. However, the high cost and vulnerability of the Ir and Ru metals are the main hostiles to use them for marketization. Herein, a high-performance OER electrocatalyst consisting of NiCo alloy nanoparticles supported on high surface area N-doped porous graphene (NiCo/pNGr(75: 25)) is reported. The importance of the doped-N for achieving the uniform dispersion-cum-effective interaction of the size controlled NiCo alloy nanoparticles has been explicitly investigated by transmission electron microscopy, X-ray diffraction, X-ray photo electron spectroscopy, Raman, density functional theory (DFT) calculations, etc. The electrochemical analysis of NiCo/pNGr(75: 25) shows an overpotential of approximate to 260 mV at 10 mA cm(-2) with a smaller Tafel slope of approximate to 87 mV dec(-1) and long catalytic durability. DFT calculations are done to check the interaction between the NiCo alloy nanoparticles and the defective sites of pNGr and also with the doped-N, which could be attained for maintaining long catalytic durability. Furthermore, NiCo/pNGr(75: 25) is used as an OER catalyst to fabricate an electrolyzer, which works at very low potential of 1.5 V in 1 M KOH.

Nanocrystalline Fe-Fe2O3 particledeposited N-doped graphene as an activity-modulated Pt-free electrocatalyst for oxygen reduction reaction - Dhavale, Vishal M.; Singh, Santosh K.; Nadeema, Ayasha; Gaikwad, Sachin S.; Kurungot, Sreekumar (Nanoscale, 2017)

Nitrogen-doped graphene anchored with mixed growth patterns of CuPt alloy nanoparticles as a highly efficient and durable electrocatalyst for the oxygen reduction reaction in an alkaline medium - Illathvalappil, Rajith; Dhavale, Vishal M.; Bhange, Siddheshwar N.; Kurungot, Sreekumar (Nanoscale, 2017)
A highly active and durable CuPt alloy catalyst with trigonal bipyramidal and truncated cube-type mixed morphologies, anchored on the nitrogen-doped graphene (NGr) surface (CuPt-TBTC/NGr), was prepared by a simple and fast method. The obtained CuPt alloy showed improved oxygen reduction reaction (ORR) activity, with a 30 mV positive shift in the half-wave potential value, as compared to the state-of-the-art Pt/C catalyst in a 0.1 M KOH solution. The CuPt alloy with the trigonal bipyramidal morphology possesses porous type inter-connected sides, which help to achieve improved mass transport of oxygen during the ORR. The exposure of the (111) plane of the CuPt alloy further improved the catalytic activity towards the dioxygen reduction in alkaline media. The ORR activity of the NGr-supported CuPt alloy was found to be dependent on the reaction time, and improved activity was obtained on the material derived at a reaction time of 90 min (CuPt-TBTC/NGr-90). The material synthesized at a lower or higher reaction time than 90 min resulted in a partially formed trigonal bipyramidal morphology with more truncated cubes or agglomerated trigonal bipyramidal and truncated cubes with closed type structures, respectively. Along with the high intrinsic ORR activity, CuPt-TBTC/NGr-90 displayed excellent electrochemical stability. Even after repeated 1000 potential cycling in a window ranging from 0.10 to 1.0 V (vs. RHE), the system clearly outperformed the state-of-the-art Pt/C catalyst with 15 and 60 mV positive shifts in the onset and half-wave potentials, respectively. CuPt-TBTC/NGr-90 also exhibited 2.1 times higher mass activity and 2.2 times higher specific activity, compared to Pt/C at 0.90 V (vs. RHE). Finally, a zinc-air battery fabricated with the alloy catalyst as the air electrode displayed a peak power density of 300 mW cm(-2), which is much higher than the peak power density of 253 mW cm(-2) obtained for the state-of-the-art Pt/C catalyst as the air electrode.

NiZn double hydroxide nanosheet-anchored nitrogen-doped graphene enriched with the gamma-NiOOH phase as an activity modulated water oxidation electrocatalyst - Nadeema, Ayasha; Dhavale, Vishal M.; Kurungot, Sreekumar (Nanoscale, 2017)
Herein, we report a facile solvothermal process to synthesize an active electrocatalyst for the oxygen evolution reaction (OER) in an alkaline medium by anchoring nanosheets of a NiZn double hydroxide over nitrogen doped reduced graphene oxide after enriching the system with the γ-NiOOH phase. This catalyst possesses a thin, porous and open layered structure, which makes the system more efficient and accessible for a better electrochemical water oxidation reaction. Moreover, we experimentally demonstrated that incorporation of Zn via a single-step solvothermal method provides an easy approach to obtain plenty of exposed γ-NiOOH phases to make the system more viable for OER with a small overpotential of 290 mV at 10 mA cm−2 and a Tafel slope of 44 mV per decade. In addition to this, the oxophilic nature of Zn in the (Zn)Ni-LDH/N-rGO catalyst helps to improve the long-term stability of the whole system. The obtained results open up possibilities for the design of future robust OER electrocatalysts by the use of very cheap and abundant materials like Ni and Zn in place of expensive Ir and Ru in the present commercial electrocatalysts.
Keywords: catalysis; Efficient Electrocatalyst; kinetics; Metal; Nickel-Hydroxide; oxide; Oxygen Evolution Reaction; performance; XPS Spectra; zinc

Proton conduction in a hydrogen-bonded complex of copper(II)-bipyridine glycoluril nitrate - Tayade, Sakharam B.; Dhavale, Vishal M.; Kumbhar, Avinash S.; Kurungot, Sreekumar; Loennecke, Peter; Hey-Hawkins, Evamarie; Pujari, Bhalchandra (Dalton Transactions, 2017)
Bipyridine glycoluril (BPG), a urea-fused bipyridine tecton, forms a square-pyramidal secondary building unit with copper(II) which further self-assembles to give a porous hydrogen-bonded complex. This complex displays a high proton conductivity of 4.45 x 10(-3) S cm(-1) at 90 degrees C and 95% relative humidity (RH). Chains consisting of coordinated water, solvent water and nitrate anions embedded in the complex are responsible for high proton conduction. The proton conduction pathway was corroborated by ab initio electronic structure calculations with molecular dynamics (MD) simulations using the Nudged Elastic Band (NEB) method. The theoretical activation energy estimated to be 0.18 eV is in close agreement with the experimental value of 0.15 eV which evidences a Grotthuss proton hopping mechanism. We thus demonstrate that the hydrogen-bonded complex encapsulating appropriate counter ions, coordinated water and solvent water molecules exhibts superprotonic conductivity.

Substituent‐induced deformed ni–porphyrin as an electrocatalyst for the electrochemical conversion of water into dioxygen - Krishna, J. V. S.; Krishna, Narra Vamsi; Singh, Santosh K.; Shaw, Pankaj K.; Dhavale, Vishal M.; Vardhaman, Anil Kumar; Giribabu, Lingamallu (European Journal of Inorganic Chemistry, 2018)
The electrochemical water oxidation ability of complexes 5,15‐diphenylporphinatonickel(II) (A) and 5,15‐bis(3,5‐di‐tert‐butylphenyl)porphinatonickel(II) (B) in the oxygen evolution reaction (OER) have been investigated in an alkaline medium. Complex B was found to be kinetically and thermodynamically more active than complex A. The overpotential and Tafel slope of complex B are lower than those of complex A by 30 mV and around 45 mV/decade, respectively, which supports the higher activity of B. Moreover, stability tests endorse the sustainability of both samples under alkaline conditions. It has been found that the 3,5‐di‐tert‐butylphenyl substituent in B plays a decisive role in achieving a better OER onset potential and current than that obtained with A, which is a result of the modulation of the structural parameters of B. Furthermore, the measured OER activities of A and B have been correlated with their molecular arrangement as well as differences in their bonding characteristics and dipole moments. For further insight, the obtained results have been confirmed by a theoretical study.

Water mediated proton conductance in a hydrogen-bonded Ni(II)-bipyridine-glycoluril chloride self-assembled framework - Tayade, Sakharam B.; Bhat, Satish S.; Illathvalappil, Rajith; Dhavale, Vishal M.; Kawade,Vitthal A.; Kumbhar, Avinash S.; Kurungot, Sreekumar; Näther, Christian (CrystEngComm, 2018)
Proton conducting properties have been investigated in a new Ni(II)-based hydrogen-bonded porous framework synthesized using a urea-fused bipyridine-glycoluril (BPG) tecton. This hydrogen-bonded self-assembled structure encapsulates water molecules in the channels with hydrogen-bonding networks which exhibits a significant temperature dependent proton conductance of 1.5 × 10−4 S cm−1 at 95 °C and 95% RH with a low activation energy (Ea) of 0.54 eV, implying a Grotthuss proton hopping mechanism mediated by hydrogen-bonded water molecules in the channels. In addition, this framework exhibited a very high water uptake under humid conditions. A continuous array of water molecules and chloride ions embedded in the highly hydrophilic porous channels of the hydrogen-bonded framework acts as the proton conducting medium.